2019
DOI: 10.1080/02656736.2019.1574985
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the survival impact of multimodal anesthesia/analgesia technique in adults undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy: a propensity score matched analysis

Abstract: Background: Studies suggest volatile anesthetics and opioids may enhance the malignant potential of cancer cells. The objective of this single institution retrospective study was to evaluate the survival impact of a multimodal opioid-sparing nonvolatile anesthetic technique (MA) in a group of patients who had undergone cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) for appendiceal carcinomatosis. Methods: Propensity score matching (PSM) and Cox proportional hazard models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Preoperative medications include multimodal pain medications and anxiolytics. Only one retrospective study has studied use of multimodal analgesia in 373 patients undergoing CRS with a combination of celecoxib 200e400 mg, pregabalin 75 mg and tramadol 100 mg [76]. These medications in combination with intraoperative non-opioid analgesia like lidocaine infusions, ketamine and dexmedetomidine, reduced postoperative opioid consumption by almost 90% and length of hospital stay by 4e5 days.…”
Section: Pre-anaesthetic Medicationmentioning
confidence: 99%
“…Preoperative medications include multimodal pain medications and anxiolytics. Only one retrospective study has studied use of multimodal analgesia in 373 patients undergoing CRS with a combination of celecoxib 200e400 mg, pregabalin 75 mg and tramadol 100 mg [76]. These medications in combination with intraoperative non-opioid analgesia like lidocaine infusions, ketamine and dexmedetomidine, reduced postoperative opioid consumption by almost 90% and length of hospital stay by 4e5 days.…”
Section: Pre-anaesthetic Medicationmentioning
confidence: 99%
“…[33] The survival benefit of opioid sparing TIVA was only demonstrated in low-volume diseases and lower American Society of Anesthesiologists (ASA) physical status patients. [313234] Use of nitrous oxide during CRS-HIPEC is not evaluated and many researchers and practitioners are using it routinely. Guidelines for anaesthetic management are summarised in Table 3.…”
Section: Anaesthetic Techniques and Monitoringmentioning
confidence: 99%
“…Because of the anti-metastatic effects of TIVA in experimental conditions, there has been a growing interest in translating such beneficial effects into human studies. 6,9,85,125,[128][129][130][131][132][133][134][135][136][137][138][139][140][141][142] The most extensive study was conducted by Wigmore et al, who retrospectively reviewed the impact of propofol-based general anesthesia vs volatile anesthesia in more than 7000 patients. 6 The authors reported a significant benefit in overall survival (HR 95% CI: 1.59, 1.30-1.95) in patients receiving propofol, even after adjusting for metastatic disease.…”
Section: General Anesthetics and Cancer Progression Volatile Anestheticsmentioning
confidence: 99%